Wednesday
March 29, 2017

Post a New Question

Posted by on .

solve exponential equation. express in exact form.
e^x-42e^-x= -19

  • precalculus - ,

    multiply each term by e^x

    (e^x)^2 - 42 + 19e^x = 0
    let y = e^x
    y^2 + 19y - 42 = 0
    (y+21)(y-2) = 0
    y = -21 or y = 2

    so e^x = 2
    x = ln 2

    or

    e^x = -21, which has no solution

    x = ln2

  • precalculus - ,

    thanks again

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question